Lactic acid bacteria isolated from artisanal dry sausages: Characterization of antibacterial compounds and study of the factors affecting bacteriocin production - Castro, Marcela Paola (2011)
Lactic acid bacteria (LAB) were isolated from artisanal dry sausages sampled from north-eastern region of Chaco, Argentina. Among 141 isolates, 27 showed antimicrobial activity against Listeria innocua, Staphyloccus aureus or Brochothrix spp. One isolate, identified as Lb. curvatus/sakei, produced bacteriocin like substances (BLIS). These BLIS were heat stable, effective after refrigerated storage and freeze/thaw cycles and even active against pathogens when produced under refrigeration at 3% NaCl concentration. The influence of several factors on production of BLIS was assessed in MRS broth added with: EDTA, ascorbic acid, KCl, potassium sorbate, sodium citrate, 3 and 6% NaCl, Tween 20 or Brij 35. These additives showed different effects towards the effectiveness of the bacteriocin produced by Lb. sakei/curvatus against L. innocua and S. aureus. Conditions that provided high cell density favored high bacteriocin production. BLIS production by this LAB strain was greatly influenced by NaCl concentration and the presence of surfactants.